Effect of type and amount of dietary carbohydrate on biomarkers of glucose homeostasis and C reactive protein in overweight or obese adults: results from the OmniCarb trial. Issue 1 (14th November 2016) - Juraschek, Stephen P; Miller, Edgar R; Selvin, Elizabeth; Carey, Vincent J; Appel, Lawrence J; Christenson, Robert H; Sacks, Frank M
Abstract : Objective: The glycemic index (GI) of dietary carbohydrate is thought to affect glucose homeostasis. Recently, the Effect of Amount and Type of Dietary Carbohydrates on Risk for Cardiovascular Heart Disease and Diabetes Study (OmniCarb) trial reported that a low-GI diet did not improve insulin sensitivity. We conducted this ancillary study of the OmniCarb trial to determine the effects of GI and carbohydrate content on glucose homeostasis and inflammation. Research design and methods: OmniCarb was a randomized cross-over feeding study conducted in overweight or obese adults without diabetes (N=163). Participants were fed each of 4 diets for 5 weeks with 2-week washout periods. Weight was held constant. Diets were: high GI (GI≥65) with high carbohydrate (58% kcal), low GI (GI≤45) with low carbohydrate (40% kcal), low GI with high carbohydrate, and high GI with low carbohydrate. We measured glycated albumin (GA), fructosamine, and high sensitivity C reactive protein (CRP) at baseline and following each dietary period. These biomarkers were compared within-person between diets. Results: The study population was 52% female and 50% black. Mean age was 53 (SD, 11) years; mean body mass index was 32 (SD 6) kg/m 2 . Reducing GI had no effect on GA or fructosamine, but increased fasting glucose in the setting of a high-carbohydrate diet (+2.2 mg/dL; p=0.02). Reducing carbohydrate content decreased GA in the setting of a high-GI diet (−0.2%; p=0.03) and decreased fructosamine in the setting of a low-GI diet (−4 µmol/L; p=0.003). Reducing carbohydrate while simultaneously increasing GI significantly reduced both GA (−0.2%; p=0.04) and fructosamine (−4 µmol/L; p=0.009). Neither reducing GI nor amount of carbohydrate affected insulin or CRP. Conclusions: Reducing carbohydrate, regardless of high or low GI, decreased GA and fructosamine. This suggests that reducing carbohydrate content, rather than GI, is a better strategy for lowering glycemia in adults at risk for diabetes. Trial registration number: NCT00608049 .